Meningkatkan Minat Belajar Siswa Kelas VII pada Materi Teks Prosedur dengan Model Problem Based Learning di SMP Negeri 2 Simpang Kiri - Epriadi Epriadi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The aim of this research is to increase class VII students' interest in learning procedural text material using a problem-based learning model at SMP Negeri 2 Simpang Kiri. This research uses descriptive research methods combined with classroom action research (ACR) methods. The results of the research are (1) a problem-based learning model, namely. a series of learning activities that emphasize the process of solving problems faced scientifically and increase students' interest in learning. (2) In cycle I there were 7 students who wrote procedure texts neatly and well structured. Other students, e.g. 13 students have good procedure texts, but their writing structure is still less organized than other students. (3) The results of cycle II are known to have experienced a significant increase. Where 16 students started to be neat and followed the structure of their writing and 4 other students were still not neat and did not follow the structure of their writing.